2022
DOI: 10.3991/ijet.v17i04.28179
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions on the Use of Google Translate: Problems and Solutions

Abstract: Machine learning has globally become a trend in most educational settings. This study aims to explore students’ perceptions when using Google Translate (GT) to support their learning as well as their problems and solutions from GT. With the participation of 250 university students at a private educational institution, a 5-point Likert-scale questionnaire and a semi-structured interview were employed to examine how students perceived the use of GT in their learning process. The findings revealed that practicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Then, as Medvedev (2016) pointed out, Google Translate is applicable both inside and outside of the classroom. Furthermore, Google Translate used as a media in translation classes, saving students' time (Pham et al, 2022). In order to save time when working on translation assignments, students also strongly advise using Google Translate, which doubles as a dictionary and can translate unfamiliar phrases while also offering synonyms and word suggestions-both of which have proven to be quite helpful.…”
Section: Theme Three: Makes Student's Translation Process Easiermentioning
confidence: 99%
“…Then, as Medvedev (2016) pointed out, Google Translate is applicable both inside and outside of the classroom. Furthermore, Google Translate used as a media in translation classes, saving students' time (Pham et al, 2022). In order to save time when working on translation assignments, students also strongly advise using Google Translate, which doubles as a dictionary and can translate unfamiliar phrases while also offering synonyms and word suggestions-both of which have proven to be quite helpful.…”
Section: Theme Three: Makes Student's Translation Process Easiermentioning
confidence: 99%
“…As education is growing significantly by fusing technology, Google Translate as a tool in the teaching-learning process met the conditions for it. Several research concluded that students have a positive perspective toward the machine (Khotimah et al, 2021;Pham et al, 2022). However, the omnipresence of Google Translate as a machine translation raised concerns among the teachers.…”
Section: Use Of Google Translation Machine In Educationmentioning
confidence: 99%
“…GT is a free online translation tool used for translating words, phrases, or web pages, and accessible via two platforms: the web interface and mobile applications (Android and iOS) and is based on Statistical Machine Translation; so instead of doing word-for-word translation, the system calculates the probabilities of various translations of a phrase being correct (Pham, 2022). GT allows users to enter the source language in a variety of ways, including using a virtual keyboard, voice recognition, handwriting, the complete document, or the entire uploaded le (Pham, 2022).…”
Section: Secondary Sources Of Datamentioning
confidence: 99%